THE EXTENSION WORKERS’ COMPETENCY IN DEVELOPING SMALL AGRIBUSINESS CAPITAL IN THE DISTRICT OF BOGOR, WEST JAVA - Fini Murfiani; Amri Jahi (Jurnal Penyuluhan, 2006)
Extension agents had to develop their competencies in promoting small agribusiness capital. They needed this new skill so they could assist small farmers to develop their agribusinesses. Every enterprise – what ever its scale -- needed capital. In conjunction with this, the objectives of this research were: (1) to describe the distribution of extension agents on selected characteristics, (2) to identify the agents’ competencies in promoting small agribusiness capital, as well as (3) to analyze the relationship of the agents’ characteristics and their competencies in promoting small agribusiness capital. Data were collected through interviews with the agents. The obtained data were analyzed by using qualitative as well as quantitative procedures. The research results demonstrated that: firstly, the Extension agents mostly indicated their generic competencies in Agricultural Extension, and lack in specific competencies in farm management, especially in small agribusiness capital formation. Secondly, agents considered promoting the small farmers self-help capability, facilitating the promotion of village financial institution, and evaluating extension program as the three most important competencies, and thirdly, regardless of their characteristics, most of the agents interviewed agreed to the rank order of nine competency areas.